Exploring the Value of Plant Analysis to Enhance Water Use Efficiency in Southwest Kansas - A. J. Foster; I. Kisekka; B. Golden (Kansas Agricultural Experiment Station Research Reports, 2017)
Nutrient deficiency is identified by use of visual symptoms. However, the application of the proposed deficient nutrient often does not result in the correction of the observed visual symptoms. This is because essential nutrients do not operate independently of each other or independently of the overall plant health and growing conditions. A study was initiated in 2016 at the Kansas State University Southwest Research-Extension Center Finnup Farm near Garden City, KS, to use both soil and plant analyses to identify toxicities or hidden deficiencies that could be limiting corn yield at various irrigation capacities. Soil samples prior to planting and plant samples at tasseling were collected from corn grown under five irrigation capacities and dryland conditions. Irrigation capacities were 0.25, 0.17, 0.13, 0.10, and 0.08 in./d. Relationships among plant nutrients and corn yield were developed to identify possible nutrients that could be limiting corn yield. Soil analysis showed soil pH of around 8 and organic matter of around 2%. In general, as expected, soil pH did increase with reduction in irrigation capacity. Sulfur (S) was the only nutrient found to be of concern within the soil analysis. Sulfur was also found to be of concern in the plant analysis. The S concentration was right at the lower limit of the sufficiency level. All other nutrients were within the required sufficiency level. However, manganese (Mn) (110 ppm) concentration was found to be higher than that of iron (Fe) (94 ppm). Whenever Mn concentration in a plant is higher than that of Fe regardless of concentration, it is an indication of Fe deficiency. Moreover, a significant relationship (P = 0.05) was observed for plant Fe concentration and corn grain yield at the 10% significance level. Likewise, an even stronger significant relationship (P = 0.035) was observed for Fe/Mn ratio and corn grain yield at the 5% significance level. These results suggest that Fe deficiency could be the hidden deficiency limiting corn yield.
Keywords: water use efficiency; plant analysis; soil analysis; iron; manganese